Oxidative stability, oxidation pattern and α-tocopherol response of docosahexaenoic acid (DHA, 22:6n-3)-containing triacylglycerols and ethyl esters - Ahonen Eija; Damerau Annelie; Suomela Jukka-Pekka; Kortesniemi Maaria; Linderborg Kaisa M (Elsevier, 2022)
DHA is most often used in supplements either in its triacylglycerol or ethyl ester form. Currently, there is only little published data on the differences in the oxidative stability and α-tocopherol response between the two lipid structures, as well as on the oxidation patterns of pure DHA. This study investigated the oxidative stability, α-tocopherol response and oxidation pattern of DHA incorporated in triacylglycerols and as ethyl esters with an untargeted approach after oxidation at 50 °C in the dark. Liquid and gas chromatographic methods with mass spectrometric detection and nuclear magnetic resonance spectroscopy were applied. DHA was more stable in triacylglycerols than as ethyl esters without α-tocopherol addition. With α-tocopherol added the opposite was observed. The oxidation products formed during triacylglycerol and ethyl ester oil oxidation were mostly similar, but also some structure-related differences were detected in both volatile and non-volatile oxidation products.